Dynamics of CO2 Emission Flux from the Vegetation Canopy Percentage in the Suropati City Park Ecosystem - Elvira, Ade Irma; Ramadhani, Muhammad Reza; Patria, Mufti Petala; Nurdin, Erwin; Vasenev, Ivan Ivanovich (ADALAH, 2025)
In recent years, fossil fuel usage and industrial activities have significantly increased, leading to higher greenhouse gas emissions and impacting global temperature, contributing to global warming and climate change. The carbon footprint measures these emissions through carbon flux rates, influenced by climate conditions, soil and water uptake, organic matter, and microbial activities. The experiment used a gas analyzer and gas chromatograph to measure samples under three conditions. The highest average flux rate was in fully enclosed vegetation (4.04 g CO2/m²/day), followed by not enclosed vegetation (4.01 g CO2/m²/day), and the lowest was 3.91 g CO2/m²/day. Results indicate that vegetation and urban parks reduce CO2 emission fluxes, with each area's vegetation state affecting soil and air temperature, pH content, and soil moisture. However, many aspects such as soil type and climate cognition can influence fluctuation of carbon fluxes in each condition.